Karakteristik asap cair yang ditambahkan ekstrak aroma daun pandan wangi (Pandanus amaryllifolius Roxb.) - Nasruddin . (Jurnal Dinamika Penelitian Industri, 2015)
This research aims to study the characteristics of liquid smoke coconut shell pyrolysis results were added aroma extract fragrant pandan leaves. Coconut shell with ± 2.5 cm size for each treatment with a weight of 10 kg to the pyrolysis temperature (T1) 300 oC, (T2) 350 oC (T3) 400 oC and (T4) 450 oC with pyrolysis time (t1) 3 hours; (t2) 4 hours; (t3) 5 hours; and (t4) 6 hours. Liquid smoke highest yield of 18.644% of all treatment is obtained from the pyrolysis at temperatures of 400 oC for 5 hours. Liquid smoke pyrolysis results of all treatments added aroma extract fragrant pandan leaves (70:30). Results of characterization of a mixture of liquid smoke to extract the best aroma of fragrant pandan leaves of all treatments is of pyrolysis at temperatures of 450 oC for 4 hours added with the aroma of fragrant pandan leaf extract with the results of a specific gravity of 1.0835, the pH value of 2.57, the acid value of 9.844%, total phenols 4.163%, and carbonyls 11.174%. The aroma of fragrant pandan leaf extract were added to the liquid smoke does not provide significant changes in aroma liquid smoke.Keywords : the scent of pandanus, liquid smoke, carbonyl, phenol, pyrolysisAbstrakPenelitian ini bertujuan untuk mempelajari karakteristik campuran asap cair dari hasil pirolisis tempurung kelapa dengan ekstrak aroma daun pandan wangi. Tempurung kelapa dengan ukuran ± 2,5 cm untuk masing-masing perlakuan dengan berat 10 kg dipirolisis pada temperatur (T1) 300 oC, (T2) 350 oC, (T3) 400 oC dan (T4) 450 oC dengan waktu pirolisis (t1) 3 jam; (t2) 4 jam; (t3) 5 jam; dan (t4) 6 jam. Rendemen asap cair tertinggi dari semua perlakuan adalah 18,644% diperoleh dari hasil pirolisis pada temperatur 400 oC selama 5 jam. Asap cair hasil pirolisis dari semua perlakuan ditambahkan ekstrak aroma daun pandan wangi (70:30). Hasil karakterisasi campuran asap cair dengan ekstrak aroma daun pandan wangi yang terbaik dari semua perlakuan adalah pirolisis pada temperatur 450 oC selama 4 jam yang ditambahkan dengan aroma ekstrak daun pandan wangi dengan hasil berat jenis 1,0835, pH 2,57, asam 9,844%, phenol total 4,163%, dan karbonil 11,174%. Ekstrak aroma daun pandan wangi yang ditambahkan pada asap cair tidak memberikan perubahan aroma yang signifikan pada aroma asap cair.Kata kunci : aroma pandan, asap cair, karbonil, phenol, pirolisis